Protection of Traditional Cloth Tapis Lampung in Communal Intellectual Property Rights Regime - Yunita Maya Putri; Ria Wierma Putri; Rehulina Rehulina (Dialogia Iuridica, 2022)
Lampung Province has a Traditional Cultural Expressions (TCE) heritage in the form of cloth “Tapis"; if it is not appropriately maintained, it will be vulnerable to being recognized by other countries that can take advantage of its existence. Currently, Indonesia regulates cloth protection in the copyright regime. However, the copyright regime has limitations in protecting it, for example, the limited time of protection provided. In addition, Tapis has Intellectual Property Rights (IPR) potential, not only in copyright-protected motifs but also in original materials and crafts that Geographical Indications can protect. So it can maintain the existence and the work of art and culture itself. In addition, the community can get economic benefits and cultural developments in Indonesia as a developing country. Based on the background above, this research will analyze the development of IPR and the construction initiative to protect Tapis Lampung. In this study, the empirical normative legal method examines and interviews the cloth weaver group through historical approaches. The data used are from laws, regulations, and interviews. Protection for Tapis Lampung can be achieved by using two measures: preventive legal protection by implementing an integrated cultural data collection system that carries out cultural recording and documentation efforts to prevent claims of intellectual property rights protection against culture. Furthermore, in repressive legal protection, rules can provide a legal basis for parties who will take action against outside parties that are considered to have taken or recognized the rights to cultural property clearly and systematically.